Analisa Kemandirian Keuangan Daerah Kota Bukittinggi Dalam Membiayai Penyelenggaraan Otonomi Daerah Tahun 2011 - Adriansyah, Adriansyah (Jurnal Ekonomi, 2013)
Regional autonomy which was promulgated with UU No. 32 of 2004 on regional government (Local Government) and UU No. 33 of 2004 on Fiscal Balance between Central and Local Government, bringing the era of centralized starting point ini initiating regional autonomy. This research is to find out how does financial independence ratio Bukittinggi City in 2011. Object of research is the achievment of financial performance targets in 2011 in Bukittinggi City Department of Finance and Asset Management Regional Bukittinggi is located on Sudirman Street. This study start from the beginning of march 2013. Independence and efectivity ratio were used in this research as analysis methode. Finally, Financial Performance of Bukittinggi in 2011 declared independence ratio by only 11,7%, which means it has not been effective/ bad for less than 50%. This means that the government of Bukittinggi is still not able to finance its own activities of government. Based on effectiveness ratio, the ability to realize revenue is budgeted to effectively target set is 93,8%, only 6,2% were not realized it means the government almost reached the set target.